Negative plate and battery

By designing a bilayer active material layer structure in the negative electrode sheet of a lithium-ion battery, using the combination of silicon-based negative electrode material and carbon-based negative electrode material, the problem of volume expansion of the silicon-based negative electrode material during the charge and discharge cycle is solved, and the energy density and circulation performance of the battery are improved.

CN119764325AInactive Publication Date: 2025-04-04EVE POWER CO LTD

Patent Information

Application Number
CN202411777760.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the volume expansion of the silicon-based negative electrode material during the charge and discharge cycle leads to structural damage, affecting the cycling performance and stability of the battery. The nanoscale materials are costly and the volume expansion of micron-scale materials is more significant.

Method used

A negative electrode sheet is designed, by designing a specific double-layer active material layer structure on at least one side of the negative electrode current collector, the inner layer uses silicon-based negative electrode material, and the outer layer uses carbon-based negative electrode material to alleviate the volume expansion effect and improve structural stability.

Benefits of technology

It effectively improves the energy density and fast charging performance of the battery, extends the service life of the negative electrode sheet, and optimizes the cycle performance and structural stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764325A_ABST
    Figure CN119764325A_ABST
Patent Text Reader

Abstract

The invention provides a negative plate and a battery. The negative plate comprises a negative current collector and a coating, and the coating is divided into an inner layer and an outer layer; the inner layer is close to the surface of the negative current collector and the outer layer is away from the surface of the negative current collector; the first negative electrode active substance of the inner layer comprises a silicon-based negative electrode material, and the silicon-based negative electrode material comprises at least one of silicon oxide, silicon carbide, nano silicon and silicon alloy. The second negative electrode active material of the outer layer comprises a carbon negative electrode material, and the carbon negative electrode material comprises at least one of natural graphite, artificial graphite, hard carbon, soft carbon, mesocarbon microbeads and graphene. By adopting the specific double-layer active material layer structure, the performance of the negative electrode is effectively improved, and the energy density and the fast charging performance of the battery are improved. Meanwhile, due to the special multi-layer structural design, the volume expansion effect of the silicon-based negative electrode material can be effectively relieved, the structural stability of the negative electrode is optimized, the structural stability of the negative electrode can be kept for a long time in the charge-discharge cycle, and then the battery performance is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a negative electrode sheet and a battery. Background Art

[0002] Lithium-ion batteries have the advantages of high voltage, high energy density, long cycle life and good safety performance, and are widely used in electric vehicles. With the development of electric vehicles, the requirements for the range, charging speed and safety performance of electric vehicle batteries are becoming higher and higher. It is urgent to develop a high-energy, high-power and high-safety lithium-ion battery.

[0003] Compared with conventional lithium battery negative electrode material graphite (theoretical specific capacity 372mA·h / g), silicon has a theoretical specific capacity of 4200mA·h / g, which can bring 20-50% energy density improvement. It is the direction of development of a new generation of negative electrode materials and has a very broad application prospect in lithium-ion battery manufacturing. However, the use of silicon materials has a major defect. During the adsorption and deintercalation cycle of lithium ions, silicon particles will produce a volume change of about 3 times. This change will cause the destruction of the surface structure of the pole piece, and then destroy the cycle performance of the battery. Therefore, in order to improve the cycle stability of silicon-based materials, some researchers use nanoscale silicon particles, nano-silicon-containing alloy materials, and blending with nano-carbon materials to improve the cycle performance of batteries. Some people also use the good conductivity, mechanical elasticity and easy control of structural modification of conductive polymers to blend them with silicon particles to buffer volume changes and improve conductivity. These measures can bring certain improvements to battery performance to a certain extent. However, the key materials in these measures are all nanoscale, which greatly increases the cost of pole piece materials. If micron-sized silicon particles are used to reduce costs, the volume expansion they bring will be more significant.

[0004] In view of this, how to further design the negative electrode to optimize the structural stability of the silicon negative electrode while improving battery capacity and energy density is of great significance to further improve the performance of current lithium batteries. Summary of the invention

[0005] In order to solve the problems and deficiencies in the prior art, the present invention provides a negative electrode sheet and a battery. In the negative electrode sheet, a specific double-layer active material layer structure is designed on at least one side of the negative electrode current collector, which effectively improves the negative electrode performance, improves the energy density and fast charging performance of the battery. At the same time, due to the special multi-layer structure design, the volume expansion effect of the silicon-based negative electrode material can be effectively alleviated, the stability of the negative electrode structure is optimized, and the negative electrode can maintain structural stability for a long time during the charge and discharge cycle, thereby optimizing the battery performance.

[0006] According to the first aspect of the present invention, a negative electrode sheet is provided, comprising a negative electrode current collector and a coating, wherein the coating is divided into an inner and outer layer; the inner layer is close to the surface of the negative electrode current collector, and the outer layer is far from the surface of the negative electrode current collector; the first negative electrode active material of the inner layer comprises a silicon-based negative electrode material, and the silicon-based negative electrode material comprises at least one of silicon oxide, silicon carbide, nano-silicon, and silicon alloy. The second negative electrode active material of the outer layer comprises a carbon-based negative electrode material, and the carbon-based negative electrode material comprises at least one of natural graphite, artificial graphite, hard carbon, soft carbon, mesophase carbon microspheres, and graphene.

[0007] In addition to the above, the prior art mostly uses the modification of negative electrode active materials to improve the performance of negative electrode materials, so as to achieve the purpose of improving battery performance. This method has a high modification cost, and the modified materials cannot be mass-produced or mass-applied, which is difficult for actual production and application and increases the production cost. In addition, the current method also increases the mass percentage of active materials by increasing the gram capacity of negative electrode active materials or increasing the thickness of the pole piece to improve the battery energy density, but this method usually adopts the traditional single-layer coating process, because the thick coating design of the pole piece will affect the wettability of the electrolyte, extend the migration path of lithium ions, and cause the battery to be charged and discharged. During the process, lithium ions cannot smoothly and quickly reach the bottom of the pole piece, forming a large concentration polarization, which in turn causes a series of problems such as the battery capacity cannot be normally exerted, poor rate performance, low-temperature lithium precipitation, and cycle capacity attenuation. In order to improve the energy density of the battery, the mainstream negative electrode active material is silicon-based negative electrode material, but the silicon volume expansion effect in silicon-based negative electrode material is large, and it is easy to break and fail during the charge and discharge cycle, and the structural stability is poor. The single-layer coating process cannot alleviate the volume expansion effect of silicon.

[0008] The present invention cleverly sets the silicon-based negative electrode material as the active material of the inner layer and the carbon-based negative electrode material as the active material of the outer layer. In this way, on the one hand, it can fully utilize the advantages of the silicon-based negative electrode material such as high specific capacity, low discharge platform, high charge and discharge efficiency, and good safety to improve the energy density and cruising range of the battery, and can fully alleviate the volume expansion effect of the silicon-based negative electrode during the charge and discharge process, improve the stability of the inner silicon-based material, and then improve the structural stability of the negative electrode sheet as a whole, improve the problems of electrode pulverization and capacity attenuation, and achieve the purpose of optimizing the battery energy density and fast charging performance at the same time. Moreover, the carbon-based negative electrode material covers the surface of the silicon-based negative electrode material, and the carbon-based negative electrode material has good conductivity, which can effectively improve the conductivity of the silicon-based negative electrode, enhance the conductivity of the negative electrode sheet as a whole, and then optimize the electrochemical performance of the silicon-based negative electrode as a whole. At the same time, the design of the inner silicon-based negative electrode material and the outer carbon-based negative electrode material is more conducive to the transmission performance of lithium ions, so that lithium ions can be quickly transmitted to the bottom of the electrode sheet, optimize the lithium ion transmission efficiency, and further improve the electrochemical performance of the silicon-based negative electrode.

[0009] Preferably, the thickness ratio of the inner layer to the outer layer is 0.05 to 0.2: 1. Ensuring that the thickness ratio of the inner layer to the outer layer is within the above range can ensure that the inner layer has a certain amount of silicon-based negative electrode material to increase the capacity and energy density of the battery, and that the outer layer has a certain thickness to alleviate the volume expansion effect of the inner silicon-based negative electrode material, taking into account the performance of the negative electrode material and the structural stability of the material, extending the service life of the negative electrode sheet, and optimizing the battery cycle performance.

[0010] Preferably, the thickness of the negative electrode sheet is 120-280 μm. The above thickness is the thickness after the electrode slurry is coated and dried.

[0011] Preferably, the sum of the thickness of the inner layer and the outer layer coated on one side is 50 to 130 μm. Controlling the sum of the thickness of the inner and outer layers within the above range is conducive to taking into account the structural stability of the entire negative electrode sheet and the capacity of the negative electrode active material, so as to achieve better comprehensive performance of the negative electrode. The above thickness is the thickness of the electrode slurry after coating and drying.

[0012] Preferably, the thickness of the negative electrode current collector is 4 to 12 μm.

[0013] Preferably, the negative electrode current collector is a porous copper foil.

[0014] Preferably, in the inner layer, the D50 of the first negative electrode active material is 0.08-20 μm; in the outer layer, when the carbon-based negative electrode material includes at least one of artificial graphite and natural graphite, the D50 of the carbon-based negative electrode material is 5-18 μm; when the carbon-based negative electrode material includes at least one of soft carbon, hard carbon, mesophase carbon microspheres, and graphene, the D50 of the carbon-based negative electrode material is 0.5-20 μm. Controlling the D50 of the first negative electrode active material and the second negative electrode active material in the inner and outer layers within the above range is conducive to taking into account the processing performance of the negative electrode sheet and the electrolyte infiltration performance. At the same time, such a particle size combination can be beneficial to the lithium ion transmission performance between the outer and inner layers, reduce polarization during charging and discharging, and optimize battery performance. Moreover, among carbon-based negative electrode materials, due to the different properties of different carbon materials, the most suitable particle size when used as negative electrode active materials is also different. Therefore, when different carbon materials are used as negative electrode active materials, their D50 is limited respectively, which is more conducive to their electrochemical performance as negative electrode active materials, and has a better synergistic effect with other materials, and is more conducive to improving the overall stability of the negative electrode sheet as well as various electrochemical properties such as conductivity and ion conductivity.

[0015] Preferably, in the inner layer, the mass proportion of the first negative electrode active material in the inner layer is 80-98%; and in the outer layer, the mass proportion of the second negative electrode active material in the outer layer is 85-98%.

[0016] Preferably, in the inner layer, the silicon-based negative electrode material includes at least one of nano-silicon and silicon carbide; in the outer layer, the carbon-based negative electrode material includes at least one of artificial graphite and mesophase carbon microspheres. The combination of the above-mentioned silicon-based negative electrode material and carbon-based negative electrode material is more conducive to fully improving the negative electrode conductivity and lithium ion transmission performance, while further improving the tight connection between the inner and outer layers, promoting the stability and bonding performance of the negative electrode sheet, and thus making the negative electrode sheet show better performance during long-term charging and discharging.

[0017] Preferably, the inner layer also includes a first conductive agent and a first binder, and the mass ratio of the first negative electrode active material, the first conductive agent and the first binder is 94.0-98.5:0.1-3.5:1.2-4.0; the first conductive agent includes carbon nanotubes; the first binder includes a first carboxymethyl cellulose and polyacrylic acid, and the mass ratio of the first carboxymethyl cellulose and polyacrylic acid is 1:3.0-4.0; the outer layer also includes a second conductive agent and a second binder, and the mass ratio of the second negative electrode active material, the second conductive agent and the second binder is 96.0-98.5:0.3-2.5:1.0-3.5; the second conductive agent includes conductive carbon black; the second binder includes a second carboxymethyl cellulose and styrene-butadiene rubber, and the mass ratio of the second carboxymethyl cellulose and styrene-butadiene rubber is 1:1.0-2.0. Carbon nanotubes have good electrical conductivity, high strength, high flexibility, high aspect ratio, and the ability to form a developed network inside the material when added in low doses. When introduced into the inner silicon-containing active layer, they can cover the surface of silicon particles and establish highly conductive and durable connections between silicon particles. Even if the volume of silicon negative electrode particles expands and begins to split, these particles can still maintain good connections through carbon nanotubes, which is conducive to extending the service life of the inner silicon material, thereby extending the service life of the negative electrode sheet and even the battery. In addition, during the coating and drying process, due to the action of capillary forces, the binder will migrate to the surface. As the coating speed increases and the surface density increases, the binder floats more seriously. The use of CMC+PAA system in the inner layer can reduce the uneven distribution of the binder caused by the floating of SBR, improve the peeling force, optimize the bonding stability of the negative electrode sheet, and improve battery performance.

[0018] Preferably, in the first binder, the mass ratio of the first carboxymethyl cellulose to the polyacrylic acid is 1:3.5.

[0019] Preferably, in the second binder, the mass ratio of the second carboxymethyl cellulose to the styrene-butadiene rubber is 1:1.5.

[0020] Preferably, the preparation method of the above-mentioned negative electrode sheet includes the following steps: S1. Mixing a first negative electrode active material, a first conductive agent, and a first binder to obtain a first negative electrode slurry, and then applying the first negative electrode slurry to one side or both sides of the negative electrode collector, drying, and obtaining an intermediate negative electrode sheet; S2. Mixing a second negative electrode active material, a second conductive agent, and a second binder to obtain a second negative electrode slurry, and then applying the second negative electrode slurry to one side or both sides of the intermediate negative electrode sheet, drying, and obtaining a negative electrode sheet; the first negative electrode slurry is applied to the surface close to the negative electrode collector, and the second negative electrode slurry is applied to the surface away from the negative electrode collector.

[0021] Preferably, the surface density K1 of the inner layer and the surface density K2 of the outer layer satisfy the following relationship: K1: K2 = 1: 6 ~ 25. By controlling the surface density of the inner and outer active material layers to meet the above-mentioned specific ratios, the reaction rate and charging performance of the negative electrode sheet can be further optimized, and the rate and cycle performance of the battery can be improved. The structural design of the inner and outer surface densities can optimize the porous structure of the electrode, shorten the transmission path of lithium ions, and provide more energy density in a smaller volume. Specifically, such a double-layer different surface density design controls the double-layer surface density to meet a specific ratio, which is conducive to ensuring that the lithium ion transmission efficiency between the upper and lower layers can achieve a better balance during the charge and discharge cycle, so that the transmission of ions and electrons is smoother, reducing the generation of lithium dendrites at the negative electrode, and then reducing the consumption of active lithium, so that the battery performance is further optimized. At the same time, such a double-layer surface density design is more conducive to the overall structural stability of the negative electrode sheet, so that it can still maintain good stability in multiple charge and discharge cycles, and improve the battery fast charging performance and cycle performance.

[0022] Preferably, K1 is 3 to 50 g / cm 2 ; K2 is 75~300g / cm 2 . Controlling K1 and K2 within the above range, firstly, can balance the mechanical properties of the inner and outer layers themselves and the lithium ion transmission performance, respectively; secondly, can achieve a better balance in the lithium ion transmission performance between the inner and outer layers, optimize the lithium ion transmission efficiency, and improve the battery performance. Moreover, controlling K1 and K2 within the above range can balance multiple performances of the negative electrode sheet, and achieve the best comprehensive performance of the negative electrode sheet, which is more conducive to the electrochemical performance of the negative electrode sheet and the battery, and improves the battery energy density, fast charging performance and cycle performance, etc. The surface density in the present invention is the surface density after the electrode slurry is coated and dried, and it is a single-sided surface density.

[0023] According to a second aspect of the present invention, a battery is provided, comprising the above-mentioned negative electrode sheet. The battery prepared using the above-mentioned negative electrode sheet has excellent lithium ion transmission efficiency and low cycle resistance, so the battery has high energy density and excellent high-rate fast charging performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the structure of the negative electrode sheet in Example 1.

[0025] The reference numerals are as follows: 1 - negative electrode current collector; 2 - inner layer; 3 - outer layer. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.

[0027] Example 1

[0028] 1. Preparation of negative electrode sheet

[0029] The negative electrode sheet of this embodiment is prepared according to the following steps:

[0030] S1. The first negative electrode active material, the first conductive agent, the first binder and water are mixed to obtain a first negative electrode slurry, and then the first negative electrode slurry is coated on both sides of the negative electrode collector (porous copper foil). After drying, an intermediate negative electrode sheet is obtained. The inner layer thickness formed by the first negative electrode slurry is 8 μm (here is the inner layer thickness on one side, and the other embodiments and comparative examples also represent this meaning), and the surface density K1 is 9 g / cm 2 (Here it refers to single-sided surface density, and the other embodiments and comparative examples also represent this meaning), the thickness of the negative electrode collector used is 5μm; the first negative electrode active material is nano-silicon, and D50 is 8.5μm; the first conductive agent is single-walled carbon nanotube SWCNT; the first binder is carboxymethyl cellulose CMC and polyacrylic acid PAA; the amounts of silicon-based negative electrode material, SWCNT, CMC, and PAA are 945g, 5g, 15g, and 35g, respectively;

[0031] S2. The second negative electrode active material, the second conductive agent, the second binder and water are mixed to obtain a second negative electrode slurry, and then the second negative electrode slurry is applied to both sides of the middle negative electrode sheet. After drying, a negative electrode sheet is obtained. The outer layer thickness formed by the second negative electrode slurry is 75 μm (here is the single-sided outer layer thickness, and the other embodiments and comparative examples also represent this meaning), and the surface density K2 is 90 g / cm 2 (Here it refers to single-surface density, and the other embodiments and comparative examples also represent this meaning); the second negative electrode active material is artificial graphite, and D50 is 13μm; the second conductive agent is conductive carbon black SP; the second binder is carboxymethyl cellulose CMC and styrene-butadiene rubber SBR; the amounts of artificial graphite, SP, CMC, and SBR are 1920g, 30g, 20g, and 30g, respectively.

[0032] In the negative electrode sheet of the present invention, the surface density is a design value, and the coating process is subsequently monitored by equipment to ensure that the coating surface density is consistent with the design value.

[0033] The schematic diagram of the structure of the negative electrode sheet in this embodiment is shown in FIG. Figure 1 , other embodiments or conforming Figure 1 The structural diagram of the comparative example is also referred to Figure 1 .

[0034] 2. Preparation of positive electrode

[0035] The positive electrode active material (NCM811 in this embodiment), the conductive agent SP and the binder PVDF are prepared into a slurry in a mass ratio of 94:3:3, coated on the aluminum foil current collector, and vacuum dried to obtain a positive electrode sheet. The surface density of the positive electrode sheet is 190g / cm 2 (Single-sided surface density tested after the electrode slurry is coated and dried), the thickness of the positive electrode active material layer is 145 μm (single-sided surface density tested after the electrode slurry is coated and dried), and the thickness of the aluminum foil current collector is 12 μm.

[0036] 3. Preparation of batteries

[0037] The prepared negative electrode sheet, positive electrode sheet, 1 mol / L LiPF6 / EC+DMC+EMC (v / v=1:1:1) electrolyte, microporous PE separator (12 μm), and shell were used to assemble the soft pack battery according to the conventional process. When assembling the battery, the negative electrode sheet and the positive electrode sheet need to be rolled before assembly.

[0038] Example 2

[0039] 1. Preparation of negative electrode

[0040] In the process of preparing the negative electrode sheet of this embodiment, the difference from that of embodiment 1 is that the coating thickness of the first negative electrode slurry and the second negative electrode slurry is adjusted so that the final inner layer thickness is 1.4 μm, the outer layer thickness is 70.0 μm, and the thickness ratio of the inner layer to the outer layer is 0.02:1. The rest of the operations are the same as those of embodiment 1.

[0041] In the negative electrode sheet of this embodiment, the surface density K1 of the inner layer and the surface density K2 of the outer layer are 1.5 g / cm 2 、84.0g / cm 2 .

[0042] 2. Preparation of positive electrode

[0043] The preparation of the positive electrode sheet in this embodiment is consistent with that in Embodiment 1.

[0044] 3. Preparation of batteries

[0045] The preparation of the battery in this example is consistent with that in Example 1.

[0046] Example 3

[0047] 1. Preparation of negative electrode

[0048] In the process of preparing the negative electrode sheet of this embodiment, the difference from that of embodiment 1 is that the coating thickness of the first negative electrode slurry and the second negative electrode slurry is adjusted so that the final inner layer thickness is 45 μm, the outer layer thickness is 90 μm, and the thickness ratio of the inner layer to the outer layer is 0.5:1. The rest of the operations are the same as those of embodiment 1.

[0049] In the negative electrode sheet of this embodiment, the surface density K1 of the inner layer and the surface density K2 of the outer layer are 49.5 g / cm 2 , 108g / cm 2 .

[0050] 2. Preparation of positive electrode

[0051] The preparation of the positive electrode sheet in this embodiment is consistent with that in Embodiment 1.

[0052] 3. Preparation of batteries

[0053] The preparation of the battery in this example is consistent with that in Example 1.

[0054] Example 4

[0055] 1. Preparation of negative electrode

[0056] In the process of preparing the negative electrode sheet of this embodiment, the difference from that of embodiment 1 is that the silicon-based negative electrode material used is adjusted to silicon carbide, and the D50 of silicon carbide is 8.5 μm, and the carbon-based negative electrode material is mesophase carbon microbeads, and the D50 of mesophase carbon microbeads is 11.0 μm. The rest of the operations are the same as those of embodiment 1.

[0057] In this embodiment, the values ​​of K1 and K2 are consistent with those in Embodiment 1.

[0058] 2. Preparation of positive electrode

[0059] The preparation of the positive electrode sheet in this embodiment is consistent with that in Embodiment 1.

[0060] 3. Preparation of batteries

[0061] The preparation of the battery in this example is consistent with that in Example 1.

[0062] Example 5

[0063] 1. Preparation of negative electrode

[0064] In the process of preparing the negative electrode sheet of this embodiment, the difference from that of embodiment 1 is that the silicon-based negative electrode material used is adjusted to silicon oxide, and the D50 of silicon oxide is 8.0 μm. The rest of the operations are the same as those of embodiment 1.

[0065] In this embodiment, the values ​​of K1 and K2 are consistent with those in Embodiment 1.

[0066] 2. Preparation of positive electrode

[0067] The preparation of the positive electrode sheet in this embodiment is consistent with that in Embodiment 1.

[0068] 3. Preparation of batteries

[0069] The preparation of the battery in this example is consistent with that in Example 1.

[0070] Example 6

[0071] 1. Preparation of negative electrode sheet

[0072] In the process of preparing the negative electrode sheet of this embodiment, the difference from that of embodiment 1 is that the carbon-based negative electrode material used is adjusted to hard carbon, and the D50 of the hard carbon is 12.0 μm. The rest of the operations are the same as those of embodiment 1.

[0073] In this embodiment, the values ​​of K1 and K2 are consistent with those in Embodiment 1.

[0074] 2. Preparation of positive electrode

[0075] The preparation of the positive electrode sheet in this embodiment is consistent with that in Embodiment 1.

[0076] 3. Preparation of batteries

[0077] The preparation of the battery in this example is consistent with that in Example 1.

[0078] Example 7

[0079] 1. Preparation of negative electrode sheet

[0080] In the process of preparing the negative electrode sheet of this embodiment, the difference from that of embodiment 1 is that the silicon-based negative electrode material used is adjusted to be a silicon alloy (Si-Al porous material), and the D50 of the silicon alloy is 18.0 μm, and the carbon-based negative electrode material is graphene, and the D50 of the graphene is 6.0 μm. The rest of the operations are the same as those of embodiment 1.

[0081] In this embodiment, the values ​​of K1 and K2 are consistent with those in Embodiment 1.

[0082] 2. Preparation of positive electrode

[0083] The preparation of the positive electrode sheet in this embodiment is consistent with that in Embodiment 1.

[0084] 3. Preparation of batteries

[0085] The preparation of the battery in this example is consistent with that in Example 1.

[0086] Comparative Example 1

[0087] 1. Preparation of negative electrode

[0088] In the process of preparing the negative electrode sheet of this comparative example, the difference from Example 1 is that according to the inner layer coating slurry ratio in Example 1, only silicon-based negative electrode material (i.e., the first negative electrode slurry) is used for coating, and the preparation process of the first negative electrode slurry is consistent with Example 1; the rest of the operations are consistent with Example 1.

[0089] In this comparative example, the surface density is consistent with the sum of the surface densities of the inner and outer layers in Example 1.

[0090] 2. Preparation of positive electrode

[0091] The preparation of the positive electrode sheet in this comparative example is consistent with that in Example 1.

[0092] 3. Preparation of batteries

[0093] The preparation of the battery in this comparative example is consistent with that in Example 1.

[0094] Comparative Example 2

[0095] 1. Preparation of negative electrode

[0096] In the process of preparing the negative electrode sheet of this comparative example, the difference from Example 1 is that according to the outer layer coating slurry ratio in Example 1, only carbon-based negative electrode material (i.e., the second negative electrode slurry) is used for coating, and the preparation process of the second negative electrode slurry is consistent with Example 1; the rest of the operations are consistent with Example 1.

[0097] In this comparative example, the surface density is consistent with the sum of the surface densities of the inner and outer layers in Example 1.

[0098] 2. Preparation of positive electrode

[0099] The preparation of the positive electrode sheet in this comparative example is consistent with that in Example 1.

[0100] 3. Preparation of batteries

[0101] The preparation of the battery in this comparative example is consistent with that in Example 1.

[0102] Comparative Example 3

[0103] 1. Preparation of negative electrode

[0104] The difference between the preparation of the negative electrode sheet of this comparative example and Example 1 is that the positions of the inner and outer layers in Example 1 are interchanged, that is, the coating order is adjusted during coating. The remaining operations are the same as those in Example 1.

[0105] 2. Preparation of positive electrode

[0106] The preparation of the positive electrode sheet in this comparative example is consistent with that in Example 1.

[0107] 3. Preparation of batteries

[0108] The preparation of the battery in this comparative example is consistent with that in Example 1.

[0109] Test Case

[0110] 1. Experimental Construction Method

[0111] The batteries prepared in all the above embodiments and comparative examples were tested for energy density, cycle capacity retention rate, capacity at different charging rates (1C, 2C, 4C) and constant current ratio. The specific test methods are as follows:

[0112] (1) Energy density:

[0113] The battery is calibrated with 0.5C / 0.5C cycle for 3 cycles, and the capacity of the last cycle is taken as the actual test capacity. Energy density = capacity*voltage / mass.

[0114] (2) Cycle capacity retention rate:

[0115] The batteries obtained in the embodiments and comparative examples were placed at 25° C. for 1 hour and then cycled at 1C / 1C with a charge and discharge voltage range of 2.5-3.6V to test the capacity retention rate of the batteries after 200 cycles.

[0116] (3) Capacity and constant current ratio at different charging rates (1C, 2C, 4C):

[0117] The batteries obtained in each embodiment and each comparative example were charged to 3.65V at 1C, 2C, and 4C constant currents, respectively, and discharged to 2.5V at 0.5C. The capacity and charging constant current ratio at 1C, 2C, and 4C were calculated. The specific calculation method is as follows: charging constant current ratio = constant current constant voltage charging capacity / constant voltage charging capacity.

[0118] 2. Experimental results

[0119] The test results of the batteries prepared in all the above embodiments and comparative examples on energy density, cycle capacity retention rate, capacity at different charging rates (1C, 2C, 4C) and constant current ratio are shown in Table 1.

[0120] Table 1 Comparison of electrical properties between the examples and the comparative examples

[0121]

[0122] It can be seen from Table 1 that the battery prepared using the negative electrode sheet prepared by the present invention has a higher energy density and cycle capacity retention rate, and the capacity and constant current are relatively high at a high rate, that is, it has a better fast charging performance, specifically refer to Examples 1 to 7.

[0123] The active materials of the negative electrode sheet of Comparative Example 1 are all silicon-based negative electrode materials, and the active materials in the two active material layers of the negative electrode sheet of Comparative Example 2 are all carbon-based negative electrode materials. The active materials are all silicon negative electrodes. During the charge and discharge process, the silicon negative electrode will undergo obvious volume expansion, which may cause damage to the internal structure of the battery and affect the battery's cycle performance and life.

[0124] In the negative electrode sheet of comparative example 3, the positions of the inner and outer layers are opposite to those of example 1, that is, the positions of the active materials in the inner and outer layers are opposite to those of example 1. This design can improve the battery energy density, but correspondingly, the battery cycle life is shorter.

[0125] Further comparing Example 1 with Examples 2 to 4, the thickness ratio of the inner layer to the outer layer in Examples 2 and 3 is not within the range of 0.05 to 0.2:1. The inner silicon negative electrode is coated thinner, and the battery energy density is difficult to be significantly improved. If it is coated thicker, the volume expansion of the silicon negative electrode is larger, and the battery cycle life is shorter. At the same time, the sum of the thickness of the inner layer and the outer layer in Example 2 is thinner, and the sum of the thickness of the inner layer and the outer layer in Example 3 is thicker, which is not conducive to taking into account the comprehensive performance of various negative electrode properties, resulting in the batteries in Examples 2 and 3 being relatively low in constant current charging at high rates, and poor high rate performance.

[0126] Comparing Example 1 with Examples 4 to 7, in Examples 4 to 7, the types of silicon-based negative electrode materials and / or carbon-based negative electrode materials are changed. It can be found that the performance of the battery in all aspects is also better when the types of silicon-based negative electrode materials and / or carbon-based negative electrode materials are changed. When the silicon-based negative electrode materials and carbon-based negative electrode materials are matched with nano-silicon and artificial graphite, or silicon oxide and artificial graphite, or nano-silicon and hard carbon, the prepared negative electrode sheet has better structural stability and ion and electron conductivity, which can be more conducive to the energy density, cycle capacity retention rate and fast charging performance of the battery. Among them, the negative electrode sheet and battery performance prepared by the combination of silicon-based negative electrode materials and carbon-based negative electrode materials is the best.

[0127] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A negative electrode sheet, characterized in that: It includes a negative electrode current collector and a coating, wherein the coating is divided into an inner layer and an outer layer; the inner layer is close to the surface of the negative electrode current collector, and the outer layer is far away from the surface of the negative electrode current collector; The first negative electrode active material of the inner layer includes a silicon-based negative electrode material, and the silicon-based negative electrode material includes at least one of silicon oxide, silicon carbide, nano silicon, and silicon alloy. The second negative electrode active material of the outer layer includes a carbon-based negative electrode material, and the carbon-based negative electrode material includes at least one of natural graphite, artificial graphite, hard carbon, soft carbon, mesophase carbon microspheres, and graphene.

2. The negative electrode sheet according to claim 1, characterized in that: The thickness ratio of the inner layer to the outer layer is 0.05 to 0.2:

1.

3. The negative electrode sheet according to claim 2, characterized in that: The sum of the thickness of the inner layer and the outer layer coated on one side is 50 to 130 μm.

4. The negative electrode sheet according to claim 1, characterized in that: In the inner layer, the D50 of the first negative electrode active material is 0.08 to 20 μm; In the outer layer, when the carbon-based negative electrode material includes at least one of artificial graphite and natural graphite, the D50 of the carbon-based negative electrode material is 5 to 18 μm; when the carbon-based negative electrode material includes at least one of soft carbon, hard carbon, intermediate carbon microbeads, and graphene, the D50 of the carbon-based negative electrode material is 0.5 to 20 μm.

5. The negative electrode sheet according to claim 1, characterized in that: In the inner layer, the mass proportion of the first negative electrode active material in the inner layer is 80-98%; In the outer layer, the second negative electrode active material accounts for 85 to 98% by mass of the outer layer.

6. The negative electrode sheet according to claim 1, characterized in that: In the inner layer, the silicon-based negative electrode material includes at least one of nano-silicon and silicon carbide; In the outer layer, the carbon-based negative electrode material includes at least one of artificial graphite and mesophase carbon microspheres.

7. The negative electrode sheet according to claim 6, characterized in that: The inner layer also includes a first conductive agent and a first binder, wherein the mass ratio of the first negative electrode active material, the first conductive agent, and the first binder is 94.0-98.5:0.1-3.5:1.2-4.0; the first conductive agent includes carbon nanotubes; the first binder includes a first carboxymethyl cellulose and polyacrylic acid, and the mass ratio of the first carboxymethyl cellulose to the polyacrylic acid is 1:3.0-4.0; The outer layer also includes a second conductive agent and a second binder, and the mass ratio of the second negative electrode active material, the second conductive agent, and the second binder is 96.0-98.5:0.3-2.5:1.0-3.5; the second conductive agent includes conductive carbon black; the second binder includes the second carboxymethyl cellulose and styrene-butadiene rubber, and the mass ratio of the second carboxymethyl cellulose to the styrene-butadiene rubber is 1:1.0-2.

0.

8. The negative electrode sheet according to claim 1, characterized in that: The surface density K1 of the inner layer and the surface density K2 of the outer layer satisfy the following relationship: K1:K2=1:6-25.

9. The negative electrode sheet according to claim 8, characterized in that: K1: 3~50g / cm 2 ; K2 is 75~300g / cm 2 .

10. A battery, characterized in that: The invention comprises the negative electrode sheet as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Negative pole piece and lithium ion battery

    CN112271283A

  • Negative pole piece as well as preparation and application thereof

    CN114400296A

  • Composite negative electrode structure and application thereof in lithium ion battery

    CN114784225A

  • Negative plate, preparation method thereof and lithium ion battery

    CN115528204A

  • Wound cell and battery

    WO2024217210A1

Cited By

  • Battery monomer and preparation method thereof, battery device and power utilization device

    CN120999086A

  • A battery cell, a method for manufacturing the same, a battery device, and a power-using device

    CN120999086B

  • Anode sheet and battery

    EP4783247A1

  • Anode sheet and battery

    WO2026118619A1